Análise da estabilidade global de edifício em concreto armado com os parâmetros γz e FAVt - Cavalheiro, Rafael (2016)
The analysis of the overall stability of buildings in reinforced concrete is considered essential today because of the need to build ever more slender buildings resulting from the increase in the vertical occupation of urban spaces. Together with the increase in height of buildings, studies related to the geometric imperfections generated by horizontal actions and non-linearity of structural behavior were intensified. The nonlinear behavior of the structure is responsible for the appearance of additional efforts on the elements, called global second order effects. In this sense, this work had as objective the use of different parameters for the evaluation of the global stability and obtaining the values of the second order effects in reinforced concrete structures. It was evaluated the use of gamma-z parameter, prescribed in NBR 6118 (ABNT, 2014), and the global stability parameter FAVt, developed by TQS Informática Ltda. The FAVt parameter considers the second order effects generated by the horizontal displacements in the nodes of the structure derived from the vertical and horizontal actions, not only the displacements caused by the horizontal actions, as is the case of the gamma-z parameter. In order to achieve the objectives, a case study was analyzed in CAD / TQS structural analysis software. From this study, other examples were derived with specific variations in the modeling to exemplify the different results in the use of the two parameters. It was possible to demonstrate that for the case study carried out, the use of the global stability parameter FAVt results in a safer second-order analysis if compared to the gamma-z parameter, a result that other authors have already demonstrated in other models.